Diagnosis of maternal Hodgkin lymphoma following abnormal findings at noninvasive prenatal screening test (NIPT): Report of two cases. Issue 3 (13th January 2021) - Castellino, Alessia; Elba, Simona; Sorasio, Roberto; Castellino, Claudia; Bonferroni, Margherita; Grasso, Mariella; Grosso, Enrico; Giacchello, Rosalba; Signorile, Anna Franca; Celeghini, Ivana; Mattei, Daniele; Mordini, Nicola; et al.
Abstract: Abnormal NIPT results, contrasting with normal fetus development, could disclose maternal malignancy, and this possibility should always be explained during pretest counseling. In this case, a complete diagnostic assessment is recommended and should be managed by a multidisciplinary team to define the best timing for diagnostic procedures, delivery, and treatment. Abstract : Abnormal NIPT results, contrasting with normal fetus development, could disclose maternal malignancy, and this possibility should always be explained during pretest counseling. In this case, a complete diagnostic assessment is recommended and should be managed by a multidisciplinary team to define the best timing for diagnostic procedures, delivery, and treatment.